Extrapulmonary manifestations of severe acute respiratory syndrome coronavirus‐2 infection. Issue 5 (1st December 2020) - Rosen, Hugo R.; O'Connell, Casey; Nadim, Mitra K.; DeClerck, Brittney; Sheibani, Sarah; DePasquale, Eugene; Sanossian, Nerses; Blodget, Emily; Angell, Trevor
Abstract: Coronavirus disease 2019, the infectious disease caused by severe acute respiratory syndrome coronavirus‐2, has resulted in a global pandemic with unprecedented health, societal, and economic impact. The disease often manifests with flu‐like symptoms and is dominated by pulmonary complications, but widely diverse clinical manifestations involving multiple organ systems can result. We posit that viral tropism and the aberrant host immune response mediate the protean findings and severity in this disease. In general, extrapulmonary manifestations are a harbinger of or contemporaneously associate with disease progression, but in the case of some extrapulmonary findings (gastrointestinal and dermatologic), may track with milder disease. The precise underlying pathophysiological mechanisms remain incompletely elucidated, and additional immune phenotyping studies are warranted to reveal early correlates of disease outcomes and novel therapeutic targets.